2007
DOI: 10.1002/jso.20684
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gadd45a and p53 proteins in human pancreatic cancer: Potential effects on clinical outcomes

Abstract: p53 and Gadd45a proteins are both highly expressed in pancreatic cancer. The overexpression of p53 and Gadd45a may have connection with the malignant biologic behavior of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Hollander et al (1999) could demonstrate that GADD45A is a component of the p53 pathway, contributing to the maintenance of genomic stability. Both p53 and GADD45A are highly expressed in human pancreatic cancer and may be associated with pivotal biological features of pancreatic cancer (Dong et al, 2005). Downregulation of GADD45A, as in our setting, reduces proliferation and induces apoptosis in pancreatic cancer cells .…”
Section: Discussionmentioning
confidence: 53%
“…Hollander et al (1999) could demonstrate that GADD45A is a component of the p53 pathway, contributing to the maintenance of genomic stability. Both p53 and GADD45A are highly expressed in human pancreatic cancer and may be associated with pivotal biological features of pancreatic cancer (Dong et al, 2005). Downregulation of GADD45A, as in our setting, reduces proliferation and induces apoptosis in pancreatic cancer cells .…”
Section: Discussionmentioning
confidence: 53%
“…GADD45α and p53 expression in clinical samples of invasive pancreatic ductal carcinomas correlated with lower survival rates for patients with GADD45α (+) subgroup compared to GADD45α (-) subgroup, suggesting a link between GADD45α and p53 expression and poor prognosis for pancreatic cancer patients [117]. Supporting this data, GADD45 proteins are highly detected in pancreatic cancer samples and those patients with positive expression of p53 and GADD45α have shorter post-operative survival rates [135]. Moreover, in pancreatic ductal adenocarcinoma, GADD45α knockdown reduces cell proliferation and induces apoptosis [136].…”
Section: Gadd45 Expression Is Deregulated In Various Types Of Cancermentioning
confidence: 93%
“…Whether these mutations have also a prognostic significance remains unclear. Few researchers have suggested a shorter overall survival in pancreatic cancer patients carrying p53 mutation compared to p53(-) patients [9,11,39,45]. In other studies though no correlation of p53 with prognosis was demonstrated [46,47].…”
Section: P-53mentioning
confidence: 95%
“…Commonly mutated genes in pancreatic cancer include K-ras (in 74-100% of cases), p16INK4a (up to 98%), p53 (43 to 76%), DPC4 (about 50%), HER-2/neu (in about 65%) and FHIT (found in 70% of cases) [9][10][11][12][13][14][15]. Other genes involved are notch1, Akt-2, BRCA2 and COX-2.…”
Section: Molecular Pathogenesis Of Pancreatic Cancermentioning
confidence: 99%